Selective chemical labeling of proteins. Issue 24 (4th March 2016) - Chen, Xi; Wu, Yao-Wen
Abstract : Diverse bioorthogonal reactions and chemical tagging approaches for protein labeling are discussed and compared in this review. Abstract : Over the years, there have been remarkable efforts in the development of selective protein labeling strategies. In this review, we deliver a comprehensive overview of the currently available bioorthogonal and chemoselective reactions. The ability to introduce bioorthogonal handles to proteins is essential to carry out bioorthogonal reactions for protein labeling in living systems. We therefore summarize the techniques that allow for site-specific "installation" of bioorthogonal handles into proteins. We also highlight the biological applications that have been achieved by selective chemical labeling of proteins.